2016
DOI: 10.1111/tmi.12662
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia in HIV‐infected pregnant women receiving triple antiretroviral combination therapy for prevention of mother‐to‐child transmission: a secondary analysis of the Kisumu breastfeeding study (KiBS)

Abstract: Abstractobjective The prevalence of anaemia during pregnancy is estimated to be 35-75% in sub-Saharan Africa and is associated with an increased risk of maternal mortality. We evaluated the frequency and factors associated with anaemia in HIV-infected women undergoing antiretroviral (ARV) therapy for prevention of mother-to-child transmission (PMTCT) enrolled in The Kisumu Breastfeeding Study 2003-2009. methods Maternal haematological parameters were monitored from 32 to 34 weeks of gestation to 2 years pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Anaemia prevalence was lower than in a study conducted in Kenya among pregnant HIV-infected women, where the prevalence of any grade of anaemia (Hb < 9.4 g/dl) was 61.8%. 20 Anaemia is the most common haematological anomaly encountered in HIV-infected patients, and has been identified as a risk factor for earlier mortality in patients with acquired immune deficiency disorder (AIDS). 21 Almost all of the mothers reported that they had easy access to HIV testing and ARVs while pregnant, which is a positive finding.…”
Section: Discussionmentioning
confidence: 99%
“…Anaemia prevalence was lower than in a study conducted in Kenya among pregnant HIV-infected women, where the prevalence of any grade of anaemia (Hb < 9.4 g/dl) was 61.8%. 20 Anaemia is the most common haematological anomaly encountered in HIV-infected patients, and has been identified as a risk factor for earlier mortality in patients with acquired immune deficiency disorder (AIDS). 21 Almost all of the mothers reported that they had easy access to HIV testing and ARVs while pregnant, which is a positive finding.…”
Section: Discussionmentioning
confidence: 99%
“…Even when it is known that AZT is not the only cause of anemia in pregnancy, and that ART is linked to improved health, particularly in lower income countries, anemia is the most common adverse effect associated with AZT use in pregnancy, independently of the regimen [ 29 – 31 ]. A study with 1070 pregnant women in sub-Saharan Africa between 2005 and 2008 reported the same results [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human immunodeficiency virus (HIV) infection and maternal anaemia are major public health problem in developing countries with extremely high prevalence in the sub Saharan Africa (SSA). 1,2 The duo occurring in pregnancy is associated with increased risk of foetomaternal morbidity and mortality. 3,4 Anaemia is said to occurs when the oxygen-carrying capacity of red blood cells is insufficient and fails to satisfy the physiologic demands of the body, and defined as haemoglobin concentration of <11.0 g/dl by WHO remains a big health challenges to safe motherhood in developing parts of Africa despite the considerable improvement in healthcare-delivery services.…”
Section: Introductionmentioning
confidence: 99%